1999
DOI: 10.1159/000017118
|View full text |Cite
|
Sign up to set email alerts
|

The Caregiving Burden Scale among Chinese Caregivers of Alzheimer Patients

Abstract: From April 1996 to January 1997, a total of 76 Alzheimer’s disease (AD) patients and their caregivers were recruited for participation in a comprehensive assessment at the Veterans General Hospital-Taipei, a 2,198-bed tertiary-care teaching hospital in Taipei, Taiwan. The AD patients responded to the Chinese version of the Cognitive Abilities Screening Instrument. Primary caregivers rated the patients using the Symptom Check List-90 (SLC-90) and the Revised Memory and Behavior Problems Checklist and then rated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 20 publications
0
39
1
Order By: Relevance
“…Research has found that spouse caregivers report higher burden than non-spouse caregivers (Deimling et al, 1989;Montgomery and Kosloski, 1994;Fuh et al, 1999). However, the current study revealed that spouses had similar odds of developing caregiver distress for all behavioral problems compared with non-spouse caregivers at each center and regardless of ethnicity.…”
Section: Discussioncontrasting
confidence: 69%
“…Research has found that spouse caregivers report higher burden than non-spouse caregivers (Deimling et al, 1989;Montgomery and Kosloski, 1994;Fuh et al, 1999). However, the current study revealed that spouses had similar odds of developing caregiver distress for all behavioral problems compared with non-spouse caregivers at each center and regardless of ethnicity.…”
Section: Discussioncontrasting
confidence: 69%
“…Cronbach's alpha for the total BPSD score was 0.816, test-retest reliability was 0.89 (p < 0.001) [34]. The scale has been extensively used as an index of the cognitive, emotional and functional impact of caregiving and showed satisfactory convergent validity [34,35,36]. …”
Section: Methodsmentioning
confidence: 99%
“…Liu et al reported a high prevalence of BPSD in Taiwanese patients with AD, and suggested that these symptoms were associated with cognitive deficits 11 . In a Taiwanese study, several clinical dementia stages 10 and more behavioral disturbances 12 were been reported to be the associative factors of caregiver burden. Huang et al 13 found that caregiver burden was significantly negatively correlated with CDR stages, and it was presumed that a patient with dementia was more difficult to take care of during the early and middle stage of disease, in which they had more BPSD.…”
Section: Introductionmentioning
confidence: 99%
“…In Taiwan, approximately 80% of the care for dementia patients is provided within the community by family members, and over half (56.6%) of main caregivers spend more than 8 hours per day caregiving 10 . Liu et al reported a high prevalence of BPSD in Taiwanese patients with AD, and suggested that these symptoms were associated with cognitive deficits 11 .…”
Section: Introductionmentioning
confidence: 99%